A calculation of capitation-based payment standardto chronic disease cases in primary care settings - Jianxiao Ni; Guangying Gao; Ning Zhao; Jin Li; Jiajie Xu; Nina Wu; Jia Yang (Chinese General Practice Journal)
Background: Outpatient medical care payment play a pivotal role in the reform of medical insurance payment methods. With ongoing reforms in China, a variety of payment strategies, including capitation and the ambulatory patient groups (APG) point method, are being progressively implemented. Objective: This study aims to identify appropriate capitation calculation methods for chronic diseases in Beijing and to provide recommendations for implementing capitation payments reforms in the city. Methods: We focused on four prevalent chronic diseases—hypertension, diabetes, coronary heart disease, and stroke—and analyzed basic medical data and public health funding in Beijing's districts C and H as case studies. This research was aimed at developing a capitation calculation method tailored to these locales, determining payment standards for major chronic diseases in primary care clinics, and thus supporting the advancement of capitation reform for outpatient chronic diseases. Results: Using medical insurance data and public health funding data from 2017 to 2019, a top-down allocation was employed to determine the capitation payment standards in district H: 4,693.11 Yuan for hypertension, 6,597.70 Yuan for diabetes, 5,644.46 Yuan for coronary heart disease, and 6,437.78 Yuan for stroke. A bottom-up costing approach was used in district C, resulting in payment standards of 4,884.18 Yuan for hypertension, 5,960.63 Yuan for diabetes, 3,733.93 Yuan for coronary heart disease, and 3,886.66 Yuan for stroke. Conclusion: The outpatient costs associated with different chronic disease populations vary considerably. In view of maintaining equity in medical insurance and the fairness of capitation fees, it is imperative to apply risk adjustments to the benchmark capitation fee. Personalized services should be tailored to the diverse types and severities of chronic diseases. It is also crucial to provide customized basic medical and public health services to various chronic disease patients as part of the capitation payment reform for outpatient services. Additionally, enhancing the capabilities of community health services in managing chronic diseases, improving contracting percentages, and establishing effective incentive and evaluation mechanisms for general practitioners are essential for equitable distribution of surplus from capitation payments.